2017
DOI: 10.1534/genetics.116.196014
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Mapping of Crossover Events in the Hexaploid Wheat Genome Suggests a Universal Recombination Mechanism

Abstract: During meiosis, crossovers (COs) create new allele associations by reciprocal exchange of DNA. In bread wheat (Triticum aestivum L.), COs are mostly limited to subtelomeric regions of chromosomes, resulting in a substantial loss of breeding efficiency in the proximal regions, though these regions carry 60-70% of the genes. Identifying sequence and/or chromosome features affecting recombination occurrence is thus relevant to improve and drive recombination. Using the recent release of a reference sequence of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(115 citation statements)
references
References 117 publications
(208 reference statements)
8
98
2
Order By: Relevance
“…Using the 35K array we see the characteristic normal distribution of CO frequency, with an average of 41-52 COs per RIL, and a non-random distribution of COs between RILs and along the chromosomes (Huang et al, 2012;Esch et al, 2007;Darrier et al, 2017). There is a positive correlation between the number of genes in the CO interval and the number of RILs with the CO suggesting that perhaps recombination in gene rich regions leads to favourable phenotypes that are under selective pressure.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Using the 35K array we see the characteristic normal distribution of CO frequency, with an average of 41-52 COs per RIL, and a non-random distribution of COs between RILs and along the chromosomes (Huang et al, 2012;Esch et al, 2007;Darrier et al, 2017). There is a positive correlation between the number of genes in the CO interval and the number of RILs with the CO suggesting that perhaps recombination in gene rich regions leads to favourable phenotypes that are under selective pressure.…”
Section: Discussionmentioning
confidence: 93%
“…It is therefore important for us to understand recombination and GC if we are to alter their rates to accelerate the induction of novel allelic combinations or to generate stable cultivars. This is particularly important in bread wheat where recombination frequency is low and skewed toward the ends of chromosomes (Darrier et al, 2017). Wheat has a large (16Gb) complex allohexaploid genome and, in the light of recent advances in the wheat's genomic and genetic resources, it presents an excellent model crop (Brenchley et al, 2012;Clavijo et al, 2017;Krasileva et al, 2017;IWGSC et al 2018.…”
mentioning
confidence: 99%
“…At this point, we can only speculate about the possible impact of meiotic recombination as a driving force towards maintaining a stable chromosome organization. Previous studies have shown that recombination in highly repetitive genomes occurs mainly in or near genes [39]. Thus, it might be important that spacing of genes is preserved for proper expression regulation or proper pairing during meiosis.…”
Section: A Stable Genome Structure Despite the Massive Reshuffling Ofmentioning
confidence: 99%
“…Rht‐B1c ( Rht3 ), Rht‐D1c ( Rht10 ), Rht‐B1e ( Rht11 ) and Rht‐B1p ( Rht17 ) are orthologs of Rht‐B1b or Rht‐D1b (Bazhenov et al ., ; Wu et al ., ; Divashuk et al ., ; Li et al ., ,b, ). Fine mapping and map‐based cloning in wheat have become easier following the release of the Chinese Spring (CS, a wheat variety) genomic sequences by IWGSC (Darrier et al ., ), but to date no Rht gene has been isolated by map‐based cloning.…”
Section: Introductionmentioning
confidence: 99%